FINANCIAL INCLUSION AND BANK EFFICIENCY: CROSS-COUNTRY EVIDENCE FROM ASEAN-6 BANKING SECTORS - Shukur, Nabilah Abdul; Sufian, Fadzlan (ADVANCED INTERNATIONAL JOURNAL OF BUSINESS, ENTREPRENEURSHIP AND SME’S (AIJBES), 2025)
Financial inclusion has been widely acknowledged for its role in promoting economic growth, enhancing financial stability, and reducing poverty. However, its influence on bank efficiency remains relatively underexplored. Given the pivotal role of banks in mobilizing savings and allocating financial resources, understanding this relationship is crucial. This study investigates how financial inclusion impacts bank efficiency in the ASEAN-6 banking sectors. Utilizing Data Envelopment Analysis (DEA) and Ordinary Least Squares (OLS) regression covering the period from 2013 to 2021, our analysis reveals that the relationship varies across the region. These findings highlight the need for tailored financial inclusion policies that account for the unique characteristics and needs of each country, particularly for unbanked and vulnerable groups. Such policies must be carefully crafted to support efficiency while advancing inclusion.